Effect of Natural Resources on Economic Growth in Pakistan: A Time Series Analysis - Khan, Maria (Asian Journal of Economic Modelling, 2021)
Objectives of present study are to examine the effect of natural resources and other macroeconomic factors (private investment, financial development, trade openness, inflation rate and labor force) on economic growth in Pakistan for the period 1972-2013. Employing the Autoregressive distributed lag (ARDL) bounds testing approach to cointegration, this study found positive and significant effect of natural resources on economic growth in the short run but in the long run it is negatively affected by natural resources. In the short run, private investment is positive and significant, while financial development and trade openness are negative. Furthermore, Labor force, private investment, financial development and inflation rate are positive and significant in the long run while trade openness is negative and significant. The analysis presented in this study is important for policy makers for effective resource conservation, fiscal and monetary policies as well as motivate to explore new natural resources for rising economic growth in Pakistan.